Methamphetamine‐associated psychosis: Clinical presentation, biological basis, and treatment options. (22nd August 2019) - Chiang, Mathew; Lombardi, Domenico; Du, Jiang; Makrum, Ursula; Sitthichai, Rangsun; Harrington, Amy; Shukair, Nawras; Zhao, Min; Fan, Xiaoduo
Abstract: Introduction: Methamphetamine associated psychosis (MAP) represents a mental disorder induced by chronic methamphetamine use in a subset of users. The prevalence of the disorder has increased in several countries in Europe and Asia where methamphetamine use has increased. MAP remains difficult to distinguish from primary psychiatric disorders, especially schizophrenia, creating complications in prescribing treatment plans to patients. Design: This narrative review sought to summarize difficulties related to MAP diagnosis and highlight the need for a better treatment model. Current best practices are described and potential novel therapies and future research suggested. Results: Results suggest that clear biological and clinical differences appear between patients presenting with MAP and schizophrenia and that there may exist distinct subgroups within MAP itself. MAP‐specific treatment studies have been few and have focused on the use of antipsychotic medication. Antipsychotic treatment has been shown to alleviate the psychotic symptoms of MAP but produce debilitating adverse effects and fail to adequately address methamphetamine use in patients. Conclusions: Continued identification of subgroups within the heterogenous MAP population may lead to better diagnosis, treatment, and outcomes for patients. Psychosocial therapies should be explored in addressing the cooccurring substance use and psychosis in the treatment of MAP.